Superoleophobic surfaces: design criteria and recent studies. Issue 2 (1st June 2013) - Mabry, Joseph M.; Tuteja, Anish; Kota, Arun K.
Abstract : Surfaces that display contact angles greater than 150° along with a low contact angle hysteresis for low surface tension liquids such as oils and alcohols are known as superoleophobic surfaces. Such surfaces are of interest for a diverse array of applications including self-cleaning, nonfouling, stain-free clothing and spill-resistant protective wear, drag reduction, microrobots for aqueous and chemical environments and icephobicity. Recently, significant advances have been made in understanding the criteria required to design superoleophobic surfaces. In this article, the authors discuss the roles of surface energy and roughness, the critical role of re-entrant texture and the role of hierarchical structure in fabricating superoleophobic surfaces. On the basis of this understanding, the authors also discuss two design parameters that allow for the systematic design of superoleophobic surfaces. The authors also summarize the recent studies on superoleophobic surfaces and emphasize the need for careful and diligent characterization. Finally, the authors conclude with the major challenges and opportunities for research on superoleophobic surfaces.